Repeated Aconitine Treatment Induced the Remodeling of Mitochondrial Function via AMPK–OPA1–ATP5A1 Pathway - Qiu, Li-Zhen; Zhou, Wei; Yue, Lan-Xin; Wang, Yi-Hao; Hao, Fei-Ran; Li, Peng-Yan; Gao, Yue (Frontiers in Pharmacology, 2021)
Aconitine is attracting increasing attention for its unique positive inotropic effect on the cardiovascular system, but underlying molecular mechanisms are still not fully understood. The cardiotonic effect always requires abundant energy supplement, which is mainly related to mitochondrial function. And OPA1 has been documented to play a critical role in mitochondrial morphology and energy metabolism in cardiomyocytes. Hence, this study was designed to investigate the potential role of OPA1-mediated regulation of energy metabolism in the positive inotropic effect caused by repeated aconitine treatment and the possible mechanism involved. Our results showed that repeated treatment with low-doses (0–10 μM) of aconitine for 7 days did not induce detectable cytotoxicity and enhanced myocardial contraction in Neonatal Rat Ventricular Myocytes (NRVMs). Also, we first identified that no more than 5 μM of aconitine triggered an obvious perturbation of mitochondrial homeostasis in cardiomyocytes by accelerating mitochondrial fusion, biogenesis, and Parkin-mediated mitophagy, followed by the increase in mitochondrial function and the cellular ATP content, both of which were identified to be related to the upregulation of ATP synthase α-subunit (ATP5A1). Besides, with compound C (CC), an inhibitor of AMPK, could reverse aconitine-increased the content of phosphor-AMPK, OPA1, and ATP5A1, and the following mitochondrial function. In conclusion, this study first demonstrated that repeated aconitine treatment could cause the remodeling of mitochondrial function via the AMPK–OPA1–ATP5A1 pathway and provide a possible explanation for the energy metabolism associated with cardiotonic effect induced by medicinal plants containing aconitine.